PKP-003 Evaluating prescriptive appropriateness and pharmacological interaction in elderly patients undergoing polytherapy in nursing homes. (14th February 2016) - Nurchis, C; Rusca, C; Polizzi, RV; Bianchi, C; Chiarello, T; Nobile, S
Abstract : Background: The health system faces economic sustainability challenges due to the ageing population. In fact, the elderly need more healthcare as a result of increasing chronic degenerative diseases. This calls for polytherapy, resulting in an inappropriate use of drugs and an increased risk of adverse reactions. An important step towards improving the elderly patient's quality of life and reducing the costs of the National Health Service is to implement strategies for appropriate use of drugs. Purpose: The objective was to evaluate prescriptive appropriateness and the possible pharmacological interactions in elderly patients undergoing a polytherapy regimen, with the aim of improving the patient's quality of life. Material and methods: During the first phase, the pharmacist visited the nursing homes to collect the updated therapies and diagnoses of patients. The term polytherapy can be used when a patient takes more than 5 drugs daily. Later, each individual therapy was analysed using the following criteria: the Micromedex database to evaluate possible drug interactions; Beers criteria and the Stopp criteria to evaluate the appropriateness of the prescription. Each nursing home received a report of the processed data, and doctors provided feedback in the light of the results obtained. Results: 274 patients were analysed, 81% females and 19% males. Mean age was 84 years. Patients were undergoing polytherapy in 83% of cases. Using the Micromedex Database, three main types of drug-drug interactions became evident: an increased risk of bleeding (37%), an increased risk of QT prolongation (22%) and an increased risk of serotonin syndrome (10%). The main pharmaceutical categories that were being misused were: antipsychotics (55%) and benzodiazepines (19%) from the total number of drugs detected using the Beers criteria; proton pump inhibitors (48%) and antipsychotics (29%) from the total number of drugs detected using the Stopp criteria. Conclusion: A high percentage of inappropriate prescriptions and potential pharmacological interactions emerged from the therapies analysed. This shows how important the active participation of the pharmacist is to ensure a safer use of medicines; this necessitates the specific skills of the one prescribing and the one dispensing. A multidisciplinary approach enables integration of these skills resulting in an improvement in the patient's quality of life. References and/or Acknowledgements: Beers and Stopp criteria, Micromedex Database No conflict of interest.